2015
DOI: 10.1002/2015jc011202
|View full text |Cite
|
Sign up to set email alerts
|

Spatial variability of absorption coefficients over a biogeochemical gradient in a large and optically complex shallow lake

Abstract: In order to improve robustness of remote sensing algorithms for lakes, it is vital to understand the variability of inherent optical properties (IOPs) and their mass‐specific representations (SIOPs). In this study, absorption coefficients for particulate and dissolved constituents were measured at 38 stations distributed over a biogeochemical gradient in Lake Balaton, Hungary. There was a large range of phytoplankton absorption (aph(λ)) over blue and red wavelengths (aph(440) = 0.11–4.39 m−1, aph(675) = 0.048–… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
19
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 21 publications
(21 citation statements)
references
References 88 publications
(139 reference statements)
2
19
0
Order By: Relevance
“…A different scenario was observed at 675 nm in both reservoirs, with phytoplankton dominating the absorption in Nav (59 %) and BB (89 %) and noticed by Babin et al (2003) and Riddick et al (2015).…”
Section: Absorption Budgetmentioning
confidence: 82%
See 1 more Smart Citation
“…A different scenario was observed at 675 nm in both reservoirs, with phytoplankton dominating the absorption in Nav (59 %) and BB (89 %) and noticed by Babin et al (2003) and Riddick et al (2015).…”
Section: Absorption Budgetmentioning
confidence: 82%
“…These coefficients influence the magnitude and the spectral distribution of the water-leaving reflectance. Inland waters typically present high concentration of coloured dissolved organic matter (CDOM), phytoplankton and inorganic particles (Riddick et al 2015). The mass-specific inherent optical properties (SIOPs) are considered the main source of uncertainty in the water-leaving reflectance interpretation.…”
Section: Introductionmentioning
confidence: 99%
“…The hypertrophic Kis-Balaton wetland system is believed to be responsible for much of the DOM entering the lake, largely derived from luxuriant growth and decomposition of aquatic plants. Previous research (Palmer et al, 2013;Riddick et al, 2015) has shown that CDOM is usually significantly higher close to the Zala River inflow, and decreases towards the outflow but very little is known about the seasonal dynamics of CDOM in the system. Suspended particulate matter in Lake Balaton is highly variable (spatially and temporally) due to its very shallow depth, constant mixing and susceptibility to wind-driven resuspension events (Istvánovics et al, 2004).…”
Section: Study Sitementioning
confidence: 99%
“…Previous research has shown that CDOM can be responsible for up to 80 % of light absorption in Lake Balaton (Riddick et al, 2015) in spite of the fact that the lake also has high concentrations of phytoplankton and non-algal particles (NAP). The high input of DOC from the Zala River results in elevated concentrations in the western basin relative to the remainder of the lake (from 0.169 m −1 near the outflow to 7.89 m −1 at the mouth of the Zala river).…”
Section: Dynamics Of Dissolved Organic Carbonmentioning
confidence: 99%
See 1 more Smart Citation